Фольклорні тексти як діалектографічний матеріал у сучасному українському мовознавстві - Грицевич, Юрій Васильович; Hrytsevych, Yurii V. (Львівський державний університет безпеки життєдіяльності, 2018)
У статті окреслено вагомий доробок українських мовознавців у сфері залучення в дослідницьке поле нового джерела діалектологічних студій – фольклорних текстів. Задекларовані в проаналізованих наукових студіях ідеї дослідження говіркового мовлення різних частин українського діалектного простору крізь призму фольклорних текстів сприятимуть створенню цілісної праці про характер співвідношення мови фольклору і діалектної мови та про конкретні вияви цього звʼязку на матеріалі західнополіського говору північного наріччя української мови.

The modern trends in Ukrainian dialectology studies require a revision of the principles and approaches to studying the dialects structural levels. First of all it concerns the choice of the source of the dialectographical material. The article highlights significant achievements of the Ukrainian linguists regarding the involvement of folklore texts into the dialectological studies, considering them as a new source of the research scope representing in a new way the structure of individual dialects. The suggested ideas to consider the material from various parts of the Ukrainian dialectal space through the prism of folklore texts will contribute to better understanding of this linguistic phenomenon and provide basis for the integrated research into the nature of the correlation between the language of folklore and dialectal language. A special attention was paid to the recording accuracy of valuable features of oral colloquial speech as an important condition for recording of the Ukrainian folklore. Folklore texts, aimed at preserving and accurate reproduction of the authentic folk speech, confirm the thesis that folklore is a special kind of stylistic interpretation of oral colloquial speech and also confirm the heuristic value of folklore records as a case study of the dialectal speech peculiarities. The key findings of the analyzed scientific works are of great importance for revealing the specific manifestations of this interconnection on the database of the Western-Polissian dialect as an integral part of the Northern-Ukrainian dialect of the Ukrainian language.
Folklore Texts as Dialectographical Material in Modern Ukrainian Linguistic Studies
Keywords: діалектологія; говірки; фольклорні тексти; евристична цінність; точність запису; текстоцентризм; dialectology; dialects; folklore texts; heuristic value; recording accuracy; text centrism